Screening for mutations in the muscle promoter region and for exonic deletions in a series of 115 DMD and BMD patients. Issue 2 (February 1992) - Vitiello, L; Mostacciuolo, M L; Oliviero, S; Schiavon, F; Nicoletti, L; Angelini, C; Danieli, G A
Abstract : Mutations in the muscle promoter region and exonic deletions were screened in a series of 115 unrelated DMD and BMD patients from north-east Italy. No gross mutations of the promoter region were found. In three cases in which dystrophin of normal size was expressed at low levels, the analysis of DNA sequences of the promoter region failed to detect abnormalities. The majority of deletions in coding sequences, detected by cDNA probes, occur in the deletion hot spot identified by the probe P20. Intrafamilial variability in the severity of the disease is reported and discussed.